Pitching Possibilities of Emerging Culture: Positioning Kickstarter as a Cultural Institution and its contributions to the development of Cultural Policy Framework for open digital cultural practice - Bonfield, Doireann (Irish Journal of Arts Management and Cultural Policy, 2021)
This study considers Kickstarter as a cultural institution, its socio-cultural feats’ alignment with prescriptions of ‘core cultural institutions’, all the while exposing cultural hierarchies and restrictive iterations of ‘culture’. Kickstarter’s mechanism of practice stands as an open, digital modality to financing ‘creative projects’ through a rewards system structure. Within the platform’s socio-cultural division, this mode of mediation allows for a basis of cultural production that is determined by an engaged public whose motivations may reside outside of commercial interests. Framing the mechanism of practice as a cultural institution serves to illuminate its sociocultural feats’ alignment with prescriptions of ‘core cultural institutions’, all the while exposing cultural hierarchies and restrictive iterations of ‘culture’. A dual methodological approach is undertaken; a discourse analysis is employed to deconstruct the barriers to embracing emerging cultural practices and conditions of production within cultural institutions and cultural industries discourses. The theories of Raymond Williams are applied to support the discursive analysis and comparative construction of Kickstarter’s mechanism of practice as a cultural institution. Socio-cultural dimensions of Kickstarter’s mechanism of practice, including its informal communities of engagement and public knowledge assets, are then situated within Williams’ inferences on technological mediation to cultural production. The public socio-cultural valuing processes, borne of the platform’s digital mechanism of practice, are understood as determinants to an emerging democratic, digitally-mediated course of cultural production.